Desenvolvimento das Pequenas e médias empresas do setor de serviços na saúde suplementar - Cordeiro Filho, Antonio (2006)
The Brazilian Supplemental Health System has gone through several phases since it was first established and long before any regulations. The law number 9656/98 was responsible for establishing it and for establishing the National Agency of the Supplemental Health ANS as well. After this law, many alterations and adaptations took place, among them there were many provisional remedies and dozens of norms and regulations. Economical crises and income reduction were responsible for a loss of more than six million users in the market of supplemental health. These users now have to, one more time, search for assistance at the Unique System of Health SUS (a public system). There is, therefore, idleness in this sector (which is now concentrated in great corporations) and which could favor the population, if only technical, commercial, administrative and legal alterations and innovations were introduced. The present study, with this in mind, suggests an alternative for the increase of the health services rendered in this country. It is the capitation system, associated with the sharing among the public and private sectors. That system already works in the odontological area. The study also analyses the characteristics of the high complex illnesses, which can present great impediments for the development of the supplemental health. As we consider the commercialization alternatives of this differentiated plan: The capitation , it was possible to consider changes in the market extent. We concluded that this alternative is viable and it can bring great benefits to the market of supplemental health, specially for the small operators, it can also benefit its development and, consequently, the health of the Brazilian people